Edukasi Keuangan untuk Remaja : Mempersiapkan Generasi Muda dalam Mengelola Keuangan pada Siswa Sekolah Tajaul Karomah Desa Situ Gadung Kabupaten Tangerang - Supriatna, Agus; Suhartono, Agus; Rahim, Eka (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Financial literacy among youth is a crucial foundation for shaping a financially responsible generation. However, many teenagers lack adequate knowledge and skills in managing personal finances, which can lead to poor financial decisions in adulthood. In response to this issue, a Community Service Program (PKM) titled